(untitled) - Silberschatz, Abraham (Boston, 1997)
Introduction; Entity-Relationship model; Relational model; SQL; Other relational languages; Integrity constraints; Relational database design; Object-Oriented databases; Object-Relational databases; Storage and file structure; Indexing and hashing; Query processing; Transactions; Concurrency control; Recovery system; Database system architectures; Parallel databases...
Keywords: Database management